Examination Medicine A Guide to Physician Training. - Talley, Nicholas J.; O'Connor, Simon (London : Elsevier Health Sciences APAC, 2014)
'Preparation is the key to success? Now in its seventh edition, Examination Medicine: a guide to physician training ebook has prepared generations of Fellow of the Royal Australasian College of Physicians (FRACP) candidates and medical students for their written and clinical examinations. Instructive, informative and aligned with current practice, this new ebook edition provides an overview of what to expect and what is expected of you. It shares valuable advice on how to prepare for the examinations, use your time to best effect and avoid common pitfal.
Chapter 13: The infectious disease long casePyrexia of unknown origin; HIV/AIDS; Chapter 14: Think like a physician, think like an examiner -- an approach with long case examples; Chapter 15: The short case; Chapter 16: Common short cases; The cardiovascular system; The cardiovascular examination; Notes on valve diseases; The hypertensive examination; Marfan's syndrome; Oedema; The respiratory system; The respiratory examination; Chest X-ray films; The gastrointestinal system; The abdominal examination; The haematological system; The haemopoietic examination; The endocrine system
Description based upon print version of record.
The thyroid gland
Keywords: Physical diagnosis; Medical history taking; Internal medicine; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Electronic books